THE USE OF PROBLEM-BASED LEARNING TO ENHANCE STUDENT PARTICIPATION - Haque, Marrisa Rizqil (Universitas Islam Nahdlatul Ulama Jepara, 2023)
This research aims to investigate the effect of implementing the Problem-Based Learning (PBL) method to enhance student participation in the learning process. The research utilized a classroom action research approach conducted in two cycles. Student participation was measured through the use of questionnaires and portfolio task evaluations. The data obtained from the questionnaires and portfolio assessments were quantitatively analyzed using Microsoft Excel with percentage calculations. The analysis results were described through descriptive explanations. The research involved a class consisting of 32 students from SMA Negeri 4 Malang. The results showed that the implementation of PBL successfully increased student participation. The average percentage of student participation based on the questionnaire reached 83% in cycle I and further increased to 93% in cycle II. Meanwhile, the average percentage of portfolio task completion as one aspect of participation reached 86% in cycle I and increased to 91% in cycle II. Overall, this research provides a preliminary understanding of the positive potential of PBL in enhancing student participation. This classroom action research provides practical benefits for teachers in designing and implementing learning activities that encourage active student participation. It is expected that this research can serve as a foundation for further in-depth and extensive studies, as well as promote the use of PBL in broader learning contexts.Â Â